When Collaborating in Constructive Task With Spouse: Attachment Orientation Predicts Exploratory Behavior Among Older Couples - Wang, Yan; Cao, Xiancai; Li, Fengzhan; Wang, Dahua (Frontiers in Psychology, 2021)
In order to examine the function of the attachment system in later life, this study investigated the relationships between attachment orientation and exploratory behavior during a collaborative constructive activity with one’s spouse among older adults. In total, 49 older couples completed a collaborative constructive task, and their behaviors were videotaped. Each participant’s exploratory behavior (i.e., engagement, enjoyment, and distress) was coded by independent raters. The results revealed older adults highly engaged in the collaborative activity. In addition, based on the Actor-Partner Interdependence Model, the results indicated that attachment avoidance positively predicted the individuals’ enjoyment as well as their partners’ distress during the collaborative activity. The current findings extend the literature regarding the effects of attachment on exploration from early adulthood to later life, from the workplace to family life, and from individual’s own behavior to collaborative situation.